Investigation of Thermal Stress Distribution in Laser Spot Welding Process - Abdulateef, Osamah F. (Al-Khwarizmi Engineering Journal, 2009)
The objective of this paper was to study the laser spot welding process of low carbon steel sheet. The investigations were based on analytical and finite element analyses. The analytical analysis was focused on a consistent set of equations representing interaction of the laser beam with materials. The numerical analysis based on 3-D finite element analysis of heat flow during laser spot welding taken into account the temperature dependence of the physical properties and latent heat of transformations using ANSYS code V.10.0 to simulate the laser welding process. The effect of laser operating parameters on the results of the temperature profile were studied in addition to the effect on thermal stresses and dimensions of the laser welded workpiece which showed good correlations between analytical and numerical results. It was found that the temperature gradients during laser welding are usually very large and it was viewed that very high temperature at the center of the workpiece, and is decreased very significantly as propagating along the radial direction. Also it found that the thermal residual stresses around the laser spot due to plastic strains were very small and localized within 1.0 mm range. It is concluded that the laser welding process is effective to reduce the welding residual stress. The stresses along the lateral direction of the workpiece changed from compression at the spot under the laser beam and tension away from the spot at the end of welding to tension at the spot under the laser beam and compression away from the spot when it cooled, which are in a good agreement with the published results.